2018
DOI: 10.1016/j.jid.2017.09.045
|View full text |Cite|
|
Sign up to set email alerts
|

SFRP2/DPP4 and FMO1/LSP1 Define Major Fibroblast Populations in Human Skin

Abstract: Fibroblasts produce matrix, regulate inflammation, mediate reparative processes, and serve as pluripotent mesenchymal cells. Analyzing digested normal human skin by single-cell RNA sequencing, we explored different fibroblast populations. T-distributed stochastic neighbor embedding and clustering of single-cell RNA sequencing data from six biopsy samples showed two major fibroblast populations, defined by distinct genes, including SFRP2 and FMO1, expressed exclusively by these two major fibroblast populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
316
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(347 citation statements)
references
References 30 publications
31
316
0
Order By: Relevance
“…Furthermore, they showed that the location within the dermis affects the expression of various enzymes and likely also their function. A study by Tabib and colleagues suggests a more diverse picture than initially expected . Their work revealed, next to several smaller FB populations, the presence of two major FB populations in human skin, which do not coincide with their location in either the papillary or reticular dermis .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, they showed that the location within the dermis affects the expression of various enzymes and likely also their function. A study by Tabib and colleagues suggests a more diverse picture than initially expected . Their work revealed, next to several smaller FB populations, the presence of two major FB populations in human skin, which do not coincide with their location in either the papillary or reticular dermis .…”
Section: Introductionmentioning
confidence: 94%
“…A study by Tabib and colleagues suggests a more diverse picture than initially expected . Their work revealed, next to several smaller FB populations, the presence of two major FB populations in human skin, which do not coincide with their location in either the papillary or reticular dermis . Together, recent literature on skin FBs suggests FB heterogeneity in the skin, and a sole classification of skin FBs based on the anatomical localization into papillary and reticular FBs might not be sufficient to fully understand their specific roles in skin homeostasis and tissue regeneration after injury.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the skin, distinct enrichment of fibroblast subpopulations is observed in the mouse upper and lower dermis, especially in wound repair . In both murine and human skin, scRNA sequencing identified a DPP4 (dipeptidyl‐peptidase‐4)‐rich fibroblast population that expresses type I collagen and possibly plays a role in scarification . DPP4 transcripts and protein are also recognized as a fibroblast activation marker in systemic sclerosis .…”
Section: Single‐cell Resolution Of Fibroblastsmentioning
confidence: 99%